Flanking Sound Transmission in Massive-Lightweight Connections - Wójtowicz, Agnieszka; Kamisiński, Tadeusz; Rubacha, Jarosław (Archives of Acoustics, 2026)
Assessing the impact of flanking sound transmission is one of the most significant challenges in the process of designing building partitions. Acoustic parameters declared by manufacturers of lightweight systems are subject to errors of up to several decibels – and in the case of inaccurate construction on site, these differences can reach even higher values. One factor contributing to this is the phenomenon known as flanking sound transmission, which involves the transmission of acoustic energy through partitions connected to the partition directly dividing two adjacent rooms. For this reason, estimating the resultant acoustic insulation of a partition, taking flanking paths into account, is crucial at an early stage of the design process to ensure compliance with the requirements outlined in standard recommendations, and the literature. Currently, there are regulations and studies that provide guidance on calculating the estimated reduction in acoustic insulation due to flanking transmission. However, in practice, situations arise that have not yet been addressed in standards or the literature. Examples include partitions made of plasterboard, which are among the most common types of partition walls in Poland, yet are not covered by current normative procedures, as well as glass systems. This study aims to further explore this topic by analysing the impact of combining a massive partition with flanking lightweight partitions for selected structures (glass, plasterboard with single or double panelling, with full or partial sound-absorbing material infill, and without infill) and connection types.